Análise da postura de indivíduos hemiplégicos cadeirantes em assentos de diferentes densidades por meio da fotogrametria computadorizada - Abreu, Caroline Lopes Gomes de (2012)
The use of a wheelchair after a Stroke is often necessary, in addition to facilitate the locomotion this device may help support and correct positioning in sitting posture. For this purpose, a few modifications in wheelchair may be required. These interventions, known as seating, aim to user comfort, prevention of deformities and pressures ulcers, besides the maintenance of a functional sitting posture. However, there are poor scientific evidence proving the benefits of these adaptations for individuals whit a sensory-motor impairment, especially those with hemiplegy. The goal of this study is to assess the different combinations of density foam seats in sitting posture individuals with hemiplegy caused by a Stroke. Participants were 18 adults with mean age of 63 years, seven female and 11 male. The procedure consisted in the demarcation of anatomical points in the anterior and posterior frontal plane, followed by a clinical assessment that determined in which hemisphere would be placed the higher density foam, according pelvic obliquity, each individual was shot eight times in four different situations. Photographic records were analyzed by postural analysis software CorporisPro® and data were submitted to descriptive and inferential statistical analysis. Regarding the use of different densities of foam in seat, this research demonstrated evidence of earnings not only pelvic alignment, but also on the trunk and head with the use hemiespumas of different densities. Thus, the results shown that the method employed can be an important tool to aid definition of seating strategies to be adopted by rehabilitation professionals as well as being a low cost technique and easy access and management.